Parametric Channel Estimation for LoS Dominated Holographic Massive MIMO Systems - Mojtaba Ghermezcheshmeh; Nikola Zlatanov (IEEE Access, 2023)
Holographic massive multiple-input multiple-output (MIMO), in which a spatially continuous surface is being used for signal transmission and reception, has emerged as a promising solution for improving the coverage and data rate of wireless communication systems. To realize these objectives, the acquisition of accurate channel state information in holographic massive MIMO systems is crucial. This paper proposes a channel estimation scheme based on a parametric physical channel model for line-of-sight (LoS) dominated communication in millimeter and terahertz wave bands. The proposed channel estimation scheme exploits the specific structure of the radiated beams generated by the continuous surface to estimate the channel parameters in a dominated LoS channel model. Since the number of unknown channel parameters is fixed regardless of the number of antennas, the training overhead of the proposed scheme does not scale with the number of antennas. The simulation results demonstrate that the proposed estimation scheme significantly outperforms other benchmark schemes in a poor scattering environment.